Asymptotic integration of second-order impulsive differential equations. (February 2018) - Akgöl, S.D.; Zafer, A.
Abstract: We initiate a study of the asymptotic integration problem for second-order nonlinear impulsive differential equations. It is shown that there exist solutions asymptotic to solutions of an associated linear homogeneous impulsive differential equation as in the case for equations without impulse effects. We introduce a new constructive method that can easily be applied to similar problems. An illustrative example is also given.